Affective and Cognitive Route in Social Media Marketing: Bibliometric-Thematic Review of Trust and Brand Image on Purchase Intention - ZULKIFLI, AKHMAD (Universitas Nusa Putra, 2025)
The growing integration of social media into consumer behavior has amplified the need to understand the mechanisms behind purchase intention. This study explores how Social Media Marketing influences consumer decision-making through two parallel psychological routes: the affective route, driven by trust, and the cognitive route, shaped by brand image. Although various conceptual models have been proposed in previous studies, the mediating roles of trust and brand image remain theoretically fragmented. To address this gap, a bibliometric–thematic review was conducted using 227 peer-reviewed journal articles published between 2014 and 2025. Co-word mapping was performed using VOSviewer software, followed by manual thematic synthesis. The analysis revealed six main thematic clusters: platform engagement, influencer credibility, digital trust mechanisms, e-commerce integration, brand image formation, and value perception. These clusters support the construction of a dual-route framework in which trust amplifies emotional assurance and brand image influences cognitive evaluations. Both work together to connect digital marketing activities with consumer purchase decisions. This framework offers new insights into the dual psychological mechanisms of digital persuasion and provides marketers with a strategic guide to enhancing consumer engagement through emotional and rational content design.